Phenomenological Study in the Practice of Increasing Customer Saticfaction Based on the Dimensions of Service Quality at Enggal Laris Building Materials Store - Ariansyah, Muhammad Azriel; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this study is to analyze five dimensions of service quality in increasing customer satisfaction and provide recommendations for improving service quality at Enggal Laris Building Store. Design/Method/Approach : This study uses a qualitative method with a phenomenological approach using thematic analysis techniques, sample collection using triangulation through interviews with three customers of Enggal Laris Building Store who have shopping experience and customer willingness to be interviewed. Research Finding : Enggal Laris Building Store focuses on customer convenience through extensive facilities and fast service. Well-trained employees provide support and product recommendations, fast response and friendly attitude increase satisfaction and pleasant interactions while shopping. Theoretical contribution/Originality : The contribution of this study lies in highlighting the significance of Parasuraman’s theory in understanding customer satisfaction, as it provides a comprehensive framework for evaluating service quality through five key dimensions—tangibles, reliability, responsiveness, assurance, and empathy—which directly influence customer perceptions and satisfaction. Practitionel/Policy implication : This study that Enggal Laris Building Store should apply the principles of Parasuraman's theory to improve service quality. Focus on employee training, product arrangement, and delivery service efficiency can increase customer satisfaction for continuous improvement and make the store the customer's first choice. Research limitation : The limitation of this study lies in the sampling that was only conducted at Enggal Laris Building Store, so the results obtained may not be generalizable to other building stores. In addition, this study also does not consider external factors that can affect customer satisfaction, such as market competition and developments in industry trends.